The Anticancer Effect of Sanguinarine: A Review - Fu, Chenxing; Guan, Guiping; Wang, Hongbing (Current Pharmaceutical Design, 2018)
In vitro and in vivo studies have revealed that Sanguinarine has antioxidant, anti-inflammatory, proapoptotic, and growth inhibitory effects on tumor cells of a variety of cancers. Previous research showed that sanguinarine induced apoptosis (cell death) and/or antiproliferative while reducing tumor cell antiangiogenic and anti-invasive properties. This paper describes various sanguinarine anti-cancer mechanisms, including inhibition of erroneously-activated signal transduction pathways, apoptosis, and tumor cell proliferation inhibition.
Keywords: anti-inflammatory